2018
DOI: 10.1016/j.powtec.2018.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Particle attrition mechanisms, their characterisation, and application to horizontal lean phase pneumatic conveying systems: A review

Abstract: Understanding particle attrition is vital to the optimisation of a wide range of industrial processes. Lean phase pneumatic conveying is one such process, whereby the high energy particle impacts can cause undesirable loss in product quality or change in bulk behaviour. The attrition process is resolved into a material function and a process function; the combination of these functions dictate the attrition mechanism present, and the magnitude of failure observed. Subsequently, the forces applied to the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 177 publications
0
11
0
Order By: Relevance
“…Meanwhile, for this device, the D 10 size always experienced a larger decrease than the D 50 and D 90 (P<0.05), which means all particles were broken with the production of more fine particles. The breakage during mixing and pneumatic conveying is typically associated with high-magnitude loading conditions, where the stresses applied to the particle exceed the particle strength and generate free surface area (Kotzur et al, 2018). On the contrary for the Forberg blender, the D 10 , D 50 and D 90 of FB15 and FB30 were slightly increased compared to their control sample.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, for this device, the D 10 size always experienced a larger decrease than the D 50 and D 90 (P<0.05), which means all particles were broken with the production of more fine particles. The breakage during mixing and pneumatic conveying is typically associated with high-magnitude loading conditions, where the stresses applied to the particle exceed the particle strength and generate free surface area (Kotzur et al, 2018). On the contrary for the Forberg blender, the D 10 , D 50 and D 90 of FB15 and FB30 were slightly increased compared to their control sample.…”
Section: Resultsmentioning
confidence: 99%
“…As stated above, the modeling of the experimental cumulative mass loss by Gwyn's model is poor and is needed to further improve and perfect. The particle attrition is highly correlated with its physical–mechanical properties 24 . Hence, regardless of the degree of attrition of particles under collision, the analysis can be carried out in terms of dependence on particle size and impact rate.…”
Section: Resultsmentioning
confidence: 99%
“…The particle attrition is highly correlated with its physical-mechanical properties. 24 Hence, regardless of the degree of attrition of particles under collision, the analysis can be carried out in terms of dependence on particle size and impact rate. Ghadiri deemed that the attrition propensity can provide a good explanation for this relationship.…”
Section: Attrition Characteristics For New Coupled Modelmentioning
confidence: 99%
“…To simply this research, the crack depth is approximately equal to the length of crack (h ≈ a). Substituting equations (15) and (16) into equation (10), the fractional loss per collision can be given by the following equation:…”
Section: E Parameter Of Crystal Breakage Modelmentioning
confidence: 99%
“…With the increasing collision rate, the kinetic energy increases and hence is more likely to exceed the inherent strength of the crystal. Particle strength is the minimum amount of stress that may be applied to a particle to cause macroscopic Journal of Chemistry damage to the particle structure [16]. It has been generally found that crystals can break at certain impact energies through the propagation of meridional cracks, producing a number of large fragments.…”
Section: E Sauter Mean Size and The Coefficient Of Variationmentioning
confidence: 99%